A novel analytical model for straightening process of rectangle-section metal bars considering asymmetrical hardening features. (September 2018) - Zhang, Yongquan; Lu, Hong; Zhang, Xinbao; Fan, Wei; Ling, He; Wei, Qinyu; Ma, Mingtian
The applied straightening moment and the springback after unloading with respect to the straightening process of rectangle-section metal bars have a direct influence on the straightening accuracy and efficiency. In this article, an asymmetrical hardening material model is first proposed to describe the stress–strain curves considering the asymmetrical features of yield stress and plastic hardening stage in tension and compression, and it is also compared with the traditional linear hardening material model. To accurately evaluate the elasto-plastic bending deformation and the springback in the straightening process, an analytical model for the loading and unloading moments is then established. The strain and stress distributions in elastic and plastic regions during the straightening process are also discussed in this article. Finally, the straightening experiments of rectangle-section metal bars under different heat-treated conditions are conducted on the ROSE-JZ50 straightening machine with displacement sensors, force sensors and strain gauges to validate the proposed analytical straightening model.